PERANCANGAN DAN SIMULASI PEMBUATAN CETAKAN TELAPAK KAKI PALSU - Achmad Budi Ramadhan (POLITALA PRESS, 2025)
A prosthetic foot mold can be created using CAD technology. With the help of CAD software, the creation of a prosthetic foot mold can produce multiple sizes using just one size as the initial reference. The initial shape of the prosthetic foot can be obtained through a 3D scanning method, which can then be processed by CAD software. Once the mold design is complete, a fabrication simulation process can be performed using CAM software. This method enables the mass production of permanent prosthetic foot molds quickly and efficiently.